Recommendations guidelines on the key information to be reported in studies of application of PEF technology in food and biotechnological processes. (October 2016) - Raso, J.; Frey, W.; Ferrari, G.; Pataro, G.; Knorr, D.; Teissie, J.; Miklavčič, D.
Abstract: The application of pulsed electric field (PEF) technology as a non-thermal cell membrane permeabilization treatment, was widely demonstrated widely to be effective in microbial inactivation studies, as well as to increase the rates of heat and mass transfer phenomena in food and biotechnological processes (drying, osmotic treatment, freezing, extraction, and diffusion). Nevertheless, most published papers on the topic do not provide enough information for other researchers to assess results properly. A general rule/guidance in reporting experimental data and most of all exposure conditions, would be to report details to the extent that other researchers will be able to repeat, judge and evaluate experiments and data obtained. This is what is described in the present recommendation paper. Industrial relevance: Pulsed electric field (PEF) treatment is a promising technology that has received considerable attention in food and biotechnology related applications food and biotechnology related applications of PEF include: i) "cold" pasteurization of liquid foods and disinfection of wastewater by microbial inactivation ii) PEF-assisted processing (drying, extraction or expression) Highlights: PEF treatment is affected by a large number of parameters. The broad experimental conditions and equipments used limited the comparison of results. The standardization of experimental procedure is required. Key information to be reported in microbial inactivation studies. Key information to be reported in studies of PEF-assisted processing in biotechnology.